Numerical study on the shock evolution and the spontaneous ignition of high-pressure hydrogen during its sudden release into the tubes with different angles. (1st January 2023) - Gong, Liang; Zheng, Xianwen; Yang, Shengnan; Yao, Yongzheng; Xie, Yongliang; Mo, Tianyu; Zhang, Yuchun
Highlights: Shock wave is reflected twice inside the tubes with different angles. Two shock reflection mechanisms for acute and non-acute tubes are proposed. It requires a longer time and a further distance to initiate the spontaneous ignition inside the tubes with larger angle. The flame induced by the spontaneous ignition could move upstream steadily inside the 60° angle tube. Abstract: High-pressure hydrogen storage is one of the best choices of hydrogen storage at present and in the future. However, the spontaneous ignition of high-pressure hydrogen release blocks its wide application. This paper further studies the shock evolution, temperature accumulation and spontaneous ignition inside the tubes with different angles by employing LES, RNG and EDC models, 10-step like opening process of burst disk and detailed hydrogen/air combustion mechanism. Four tubes with different angles (60, 90, 120 and 150°) are employed based on the previous experimental result. It is found that the smaller the angle of the tube, the greater the maximum pressure and temperature of the first shock reflection zone. And the maximum pressure and temperature of the second shock reflection zone is the highest inside the 90° angle tube. This is due to two shock reflection mechanisms inside the tubes: in acute angle tube, only the reflected hemispherical shock hits the inner wall of the tube corner, however, for non-acute tubes, both the reflected hemispherical shock and reflected normal shock hit the inner wall of the tube corner. In addition, it requires a longer time and a further distance to initiate the spontaneous ignition inside the tubes with larger angle. And the flame induced by the spontaneous ignition could move upstream steadily inside the 60° angle tube and the flame length increases with the release time to a maximum value of 21.44 mm.